A review of the application of CIELAB colour systems for the development of gold and silver nano-enabled colorimetric assays for the detection of chromium - Sindisiwe Fortunate Shange; Phumlane Selby Mdluli; Nirmala Deenadayalu (Results in Chemistry)
Heavy metals are hazardous to people and are linked to several serious illnesses. According to reports, water contamination poses a severe environmental risk to both people and aquatic life. As consequently, there is a critical requirement to maintain the availability of safe water for consumption and verify the potentially harmful levels of metals in water bodies. Nevertheless, finding analytical platforms that offer high sensitivity, selectivity and efficiency while being affordable, portable and user-friendly is still difficult. A powerful analytical platform that can meet these needs is CIE L*a*b*/Yxy colour systems. Today, chromium is increasingly employed in a variety of industrial processes, including as chrome plating, the creation of dyes and pigments, the tanning of leather, and the preservation of wood. It typically exists in the chromium(III) and (VI) oxidation states. One of the greatest notable characteristics of gold and silver nanoparticles is a phenomenon known as the localized surface plasmon resonance (LSPR). Due to their fundamental optical characteristics, well-spaced colloidal solutions of gold nanoparticles and silver nanoparticles exhibit higher extinction coefficients and a distinct colour in the visible portion of the spectrum than aggregated samples. As a result, the well-designed chemical interaction between the analyte and the nanoparticles surrounds allows for the visual identification of the chromium. This interaction results in a shift in colour from red to blue for gold nanoparticles and from yellow to brown for silver nanoparticles from well-spaced to aggregated ones.The purpose of this review is to give a thorough overview on the applications of the CIEAB colour systems that have been established for the gold nanoparticles and silver nanoparticles-based chromium detection. Report on the synthetic, fabrication and detection techniques chosen for these applications. Additionally, a rigorous evaluation of the photograph image processing is conducted.